Системы менеджмента качества: медицинский аудит как расширенная программа клинического аудита = Quality management system: medical audit as extended program of clinical audit - V. S. Biryukov (Kazimierz Wielki University, 2016)
Biryukov V. S. Системы менеджмента качества: медицинский аудит как расширенная программа клинического аудита = Quality management system: medical audit as extended program of clinical audit Journal of Education, Health and Sport. 2016;6(8):823-841. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.167099 http://ojs.ukw.edu.pl/index.php/johs/article/view/4000       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 26.08.2016.   СИСТЕМЫ МЕНЕДЖМЕНТА КАЧЕСТВА: МЕДИЦИНСКИЙ АУДИТ КАК РАСШИРЕННАЯ ПРОГРАММА КЛИНИЧЕСКОГО АУДИТА   В. С. Бирюков   Одесский национальный медицинский университет   Реферат Настоящая работа посвящена анализу сильных и слабых сторон клинического аудита. Полученные данные сопоставлены с возможностями аудита систем менеджмента качества (СМК) лечебных учреждений, разработанных и внедренных в соответствии с требованиями международных стандартов качества  серии ИСО 9000. Всеобъемлющий характер аудита СМК не имеет той глубины, какой обладает клинический аудит. В свою очередь, клинический аудит не рассматривает вспомогательные процессы, обеспечивающие высокое качество оказания медицинских услуг. Сделан вывод о целесообразности объединения этих типов аудита в единый медицинский аудит. Ключевые слова: клинический аудит, медицинский аудит, аудит систем качества, стандарты ISO 9000, ISO 19011.   QUALITY MANAGEMENT SYSTEM: MEDICAL AUDIT AS EXTENDED PROGRAM OF CLINICAL AUDIT V. S. Biryukov Odessa National Medical University Abstract This paper deals with analysis the strengths and weaknesses of clinical audit. The obtained data are compared with the capabilities of audit quality management systems (QMS) in medical institutions, developed and implemented  in accordance with the requirements of international quality standards ISO 9000 series. The comprehensive nature the QMS audit does not have the depth as a clinical audit. In turn, clinical audit does not consider the supporting processes, providing high quality medical services. It was concluded that the feasibility of combining these audit types into a single medical audit. Keywords: clinical audit, medical audit, quality system, ISO 9000, ISO 19011